Endothelial dysfunction in patients with acromegaly and It's association with Endocan. (February 2021) - Kul, Seref; Caklili, Ozge Telci; Tutuncu, Yasemin; Ozcan, Fatma Betul; Aksu, Feyza; Baycan, Omer Faruk; Atici, Adem; Bilgili, Ummuhan Zeynep; Takir, Mumtaz; Caliskan, Mustafa
Abstract: Objective: This study aims to assess endocan levels in patients with acromegaly who have active disease or disease in remission and to investigate a relation between endocan levels and endothelial dysfunction in these patients. Design: The study is a case-control study. Study was conducted at Istanbul Medeniyet University Goztepe Training and Research Hospital between 2013 and 2019. Patients who were older than 18 years with acromegaly diagnosis were recruited if they agreed to participate. Patients with uncontrolled diabetes (DM), hypertension (HT), hyperlipidemia, decompensated heart failure, immune or infectious diseases, moderate-severe valve disease and stage 3 or more advanced chronic kidney disease were excluded. There were 30 healthy control subjects who agreed to participate to the study. Patients with acromegaly were divided into two groups as: disease active patients and patients in remission. Serum endocan levels were measured with enzyme linked immunosorbent assay (ELISA) method endothelial function was assessed with flow mediated dilatation (FMD). Results: There were 85 patients included to the study. Twenty-three patients had active disease, 31 were in remission and 31 were healthy controls. FMD was higher in controls compared to patients in active disease and patients in remission ( p < 0.001). There was no difference between patients with active disease for FMD and patients in remission ( p = 0.088). There was statistically significant correlation between FMD and endocan and insulin like growth hormone-1 (IGF-1) levels of patients with acromegaly. As FMD increased endocan and IGF-1 decreased. A moderate negative relation between FMD and endocan was identified ( p < 0.001, r:-0.409) as well as FMD and IGF-1 levels (p:0.011, r:-0.377). Along with endocan and IGF-1, DM, HT, sex, body mass index, age and uric acid were associated with changes in FMD. Conclusions: Endocan levels and endothelial function measured with FMD have an inverse relationship. Endocan may prove to be a marker for endothelial dysfunction in acromegaly. Highlights: Acromegaly causes atherosclerosis that can reveal itself as endothelial dysfunction. Endocan is a marker of inflammation and it's associated with cardiovascular diseases. There is an association between endocan and endothelial dysfunction. Endocan can be useful to detect early signs of atherosclerosis.